Anatomical and preliminary chemical studies on the leaves of Cotinus coggyria Scop. (Anacardiaceae) - (:unkn) unknown (My University, 2007)
Cotinus coggyria Scop. is well-known with vernacular names "tetra, tetre, tetere" and used different medicinal purposes commonly by local people in Kirklareli. The leaves of C. coggyria are bifacial and hypostomatic. It has glandular (unicellular stalk-multicellular head) and nonglandular (simple, unicelular) hairs on the leaves. It is observed many druses (cluster crystals) and a few prismatic crystals. Stomata amount is 250 per mm2 on the lower surface of the leaves. The tannin, flavonoid, mucilage content of the leaves was determined.